2013
DOI: 10.1111/jerd.12052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Enamel Microabrasion for the Aesthetic Management of Mild‐to‐Severe Dental Fluorosis

Abstract: The clinical performance of enamel microabrasion is affected by the severity of dental fluorosis, except for its performance of removing brown stains. Even though its performance of improving appearance decreases with the increase in severity of fluorosis, it may not only remove the fluorosis stains but also may increase the success of additional subsequent treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 10 publications
1
28
0
5
Order By: Relevance
“…Regarding DF, 8 of the selected studies assessed the bleaching of the affected teeth, 9 analyzed the effects of enamel microabrasion, 4 evaluated the effect of a combined treatment (tooth bleaching and enamel microabrasion) and Gugnani et al used a resin infiltrant. Gupta et al and Mehta et al studied the effect of oral administration of calcium and vitamins in reducing lesion size whereas Hasanuddin et al applied fissure sealants to molars with DF.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding DF, 8 of the selected studies assessed the bleaching of the affected teeth, 9 analyzed the effects of enamel microabrasion, 4 evaluated the effect of a combined treatment (tooth bleaching and enamel microabrasion) and Gugnani et al used a resin infiltrant. Gupta et al and Mehta et al studied the effect of oral administration of calcium and vitamins in reducing lesion size whereas Hasanuddin et al applied fissure sealants to molars with DF.…”
Section: Resultsmentioning
confidence: 99%
“…Subjective evaluation parameters used in our study included scoring for “Change in esthetics” and “improvement in brown stains/opaque white areas” on a Visual Analog Scale. These VAS scales were adopted from similar studies done for evaluating the esthetic improvements in fluorosis patients . Similar VAS scales have also been used by other researchers for fluorosis and other stain removal studies …”
Section: Discussionmentioning
confidence: 99%
“…Celik et al reported that this scale can truly quantify the overall improvement in the appearance of the mottled surface and a quantitative evaluation of Δ E only on fluorotic area of the tooth may not be sufficient …”
Section: Discussionmentioning
confidence: 99%
“…Even though the esthetic perception of enamel mottling is variable across patients, this may have considerable psychosocial effects on many patients and impact their quality of life . Therefore, considerable efforts have been put in identifying an effective means to treat fluorotic stains that might be chosen according to lesion severity .…”
Section: Introductionmentioning
confidence: 99%